ANALISIS KESULITAN BELAJAR PADA MATERI SPLDV SISWA KELAS X SMK BINA INSAN BANGSA DI TINJAU DARI SEGI KEMAMPUAN KOMUNIKASI MATEMATIK - Risya Aulia Husn; Euis Eti Rohaeti; Eka Senjayawati (Departement of Mathematics Education, 2019)
The purpose of this study was to analyze the learning difficulties of mathematics in terms of students' mathematical communication skills. The nature of this research is descriptive with a qualitative approach. While the subjects in this study were 10 students from the Bina Insan Bangsa (BIB) Vocational School Ngamprah. Data collection in this study uses observation techniques, tests and interviews, while data analysis techniques in this study are data collection with observations and then processing data, presenting data and drawing conclusions. The conclusions that can be drawn in this study that the difficulties of students in learning mathematics are 2, namely; (1) the difficulty of the concept, and (2) verbal difficulties. The causes of these difficulties are because students' mathematical communication skills are low